Assessment of climate change impact on runoff and peak flow: a case study on Klang watershed in West Malaysia - Kabiri, Reza (2014)
Climate change is a consequence of changing in climate on environment over the worldwide. The increase in developmental activities and Greenhouse Gases (GHGS) put a strain on environment, resulting in increased use of fuel resources. The consequence of such an emission to the atmosphere exacerbates climate pattern. There are numerous Climate Change Downscaling studies in coarse resolution, which have largely centred on employing the dynamic approaches, and in most of these investigations, the Regional Climate Model (RCM) has been reported to numerically predict the local climatic variables. The majority of previous investigations have failed to account for the spatial watershed scale, which could generate an average value of downscaled variables over the watershed scale.